Pseudomonas halotolerans sp. nov., a halotolerant biocontrol agent with plant-growth properties - Sánchez, Patricia; Castillo, Inés; Martínez-Checa, Fernando; Sampedro, Inmaculada; Llamas, Inmaculada (Frontiers in Plant Science, 2025)
A polyphasic taxonomic approach was conducted to characterize the bacterial strain B22T isolated from the rhizospheric soil of the halophyte Salicornia hispanica. This strain is aerobic, Gram-negative, rod-shaped, catalase and oxidase positive, motile, reduces nitrates and chemoheterotrophic. It is halotolerant, exhibiting optimal growth at 28°C and pH 7.0 in the presence of 0.5-2.5% (w/v) of NaCl. The B22T genome size is 5.7 Mbp, with a G+C content of 60.5 mol%. This strain has the capacity to promote tomato growth by producing siderophores, indole-3-acetic acid and enzymes such as phytase and acid phosphatase. Additionally, strain B22T produces a quorum quenching (QQ) enzyme capable of degrading synthetic N-acylhomoserine lactones (AHLs) as well as those produced by phytopathogens. The interference of plant pathogen communication reduced virulence in tomato fruits and plants. Phylogenetic analysis revealed that the closest relatives of strain B22T was Pseudomonas tehranensis SWRI 196T. The average nucleotide identity values between strain B22T and P. tehranensis SWRI 196T was 95.1% while digital DNA-DNA hybridization values was 64.5% The main cellular fatty acids of strain B22T were C16:0, summed feature 3 (C16:1ω7c/C16:1ω6c) and summed feature 8 (C18:1ω7c/C18:1ω6c). The major polar lipids identified were diphosphatidylglycerol and phosphatidylethanolamine, while the predominant respiratory quinone was ubiquinone (Q-9). Based on genomic, phylogenetic and chemotaxonomic data, strain B22T (=CECT 31209; =LMG33902) represents a novel species within the genus Pseudomonas. The name Pseudomonas halotolerans sp. nov. is proposed. Additionally, this study highlights the potential of P. halotolerans as a sustainable biocontrol agent due to its plant growth-promoting activity in tomato plants and its ability to reduce phytopathogen virulence factors, mitigating damage to fruits and plants.